Crédito no cenário das micro e pequenas empresas no Estado de Sergipe (2009-2012) - Mendonça, Priscila Jesus (2015)
The business and economic advancement made the micro and small enterprises, they needed to be in line with the global market. And for that financial resources are needed. In order to meet the demands of the market, these resources can be obtained by own sources or through financial institutions that provide credit. Faced with the new needs of the market, micro and small companies in the state of Sergipe have sought borrowing from financial institutions as a way to foster its development. Given this scenario, we designed the following problems: Brazil´s Banco do Nordeste as developers of development in the Northeast has helped in the growth of micro and small businesses in the state of Sergipe in obtaining loans and financing of production and which impulses generated in state? This study presents the quantitative research method called panel data analysis with the variables loans: value added (agriculture, industry, services), the economically active population, average wages and formal employment in order to explain the possible development generated by micro and small companies Sergipe, to obtain credit to finance production from 2009 to 2012 and to identify the impact of these operations on employment levels of municipalities in Sergipe. The results, considering the variables applied demonstrate that the credit has no impact on job creation. The proposal for future work is to conduct a regional study considering other financial institutions.